Dragging Chains - Hvidtfeldt, Emil (Journal of Anthropological Films, 2025)
Dragging Chains moves between observation and conversation as the apparent obscurity of Grenada's Jab Jab masquerade is unraveled. Shot during the 2023 carnival season, the film immerses its viewers in a sensorial spectacle of oil, chains and rhythms, while the stories told by local practitioners provide a backdrop of contemporary interpretation. As the spectacle unfolds, the initial exotic appeal gives way to deeper questions of resilience, protest and the after-effects of slavery. The film is accompanied by a written thesis of the same name, exploring themes of storytelling, resistance and national identity formation in the post-colonial context of Grenada. Emil Victor Hvidtfeldt is a visual anthropologist from Copenhagen, Denmark. He is educated in ethnographic filmmaking with a master’s from UiT - The Arctic University of Norway. With an international outlook, he has a special interest in music, identity, (post)colonial studies, and audio-visual research. He is currently on the working committee of the Nordic Anthropological Film Association (NAFA). His master’s film, Dragging Chains, has been screened at numerous ethnographic film festivals globally.